Chromosome-level genome assembly of the parasitoid wasp Aenasius arizonensis - Wan-Ying Dong; Tian-Yu Huang; Sheng-Yuan Zhao; Juan Zhang; Yang Lei; Jun Huang; Zhong-Shi Zhou; Yao-Bin Lu (Scientific Data)
Abstract Aenasius arizonensis is an important solitary endoparasitoid successfully used for biocontrol of cotton mealybug. However, lacking genomic resources has limited molecular-level investigations. Our exploration produced a superior genomic assembly of A. arizonensis from the chromosome level by combining MGISEQ short reads, Hi-C scaffolding, and PacBio Revio sequencing techniques. The genome measured 398.69 Mb, including a contig N50 of 4.73 Mb, a BUSCO completeness level of 97.07%, and a scaffold N50 of 35.96 Mb. Hi-C data were further utilized cluster and anchor 98.66% of the genome sequences into 11 chromosomes. Approximately, 165.90 Mb, representing about 41.61% of the genome, was identified as repeat elements. Non-coding sequence annotation identified 171 rRNAs, 117 small RNAs, 331 regulatory RNAs, and 872 tRNAs. Genome annotation reveals 11,727 protein-coding genes, with 10,842 (92.45%) genes functionally annotated. In summary, our chromosome-level genome assembly serves as a significant resource for advancing research on Encyrtidae parasitoids.